Environmentally Sustainable Tourism Marketing in Emerging Economies: A Case Study of Bangladesh - Uddin, M M Mofiz (New Advances in Business, Management and Economics Vol. 3, 2025)
Background: Integrating environmental sustainability into tourism marketing aims to minimize adverse impacts while maximizing economic and socio-cultural benefits. Purpose: This study evaluates the effects of environmentally sustainable tourism marketing in Bangladesh, focusing on economic, socio-cultural, environmental, eco-tourism, and ecological aspects and the role of government activity. Methodology: Using a quantitative methodology, surveys from 200 respondents, including tourists and stakeholders in the tourism sector, were analyzed with SPSS to assess relationships between independent and dependent variables. Hypotheses were tested to examine these correlations. Findings: Environmentally sustainable tourism marketing influences economic growth, socio-cultural development, and ecological awareness, with eco-tourism and government activeness. The most significant variables (eco-tourism, ecological awareness, and government involvement) influence environmentally sustainable tourism marketing. Most respondents noted that it increases employment, supports local economies, conserves heritage, and promotes ecological balance, although challenges like environmental degradation and the need for active government involvement persist. Social Consequences and Implications: Sustainable tourism improves local quality of life, fosters better tourist-local understanding, and promotes cultural preservation, emphasizing public awareness and community participation. Findings suggest that policymakers and marketers can prioritize sustainability (developing eco-tourism sites and policy framework, implementing eco-tourism certification, providing incentives for sustainability practices) for long-term value. Research Limitations: The study’s focus on Bangladesh may limit generalizability. Further research is needed across different contexts. Originality: This research provides empirical evidence from an emerging economy, offering insights into increasing sustainability in tourism.